RELATIONSHIP BETWEEN THYROID DISEASE AND TYPE 2 DIABETES - Khalilov Hikmatulla Dilshodovich; Kayimov Mirzohid Normurotovich; Esanov Alisher Akromovich (Journals Park Publishing, 2023)
Diabetes and thyroid disease result from endocrine dysfunction, and both have been shown to interact. Changes in thyroid hormone levels, even within the normal range, can trigger the onset of type 2 diabetes (T2D), especially in people with prediabetes. The aim of this review is to understand the pathological relationship between thyroid-related diseases and T2D. Thyroid-related diseases and T2D are closely related. Type 2 diabetes can be exacerbated by thyroid disorders, and diabetes can worsen thyroid dysfunction. Insulin resistance has been found to play a critical role in T2D and thyroid dysfunction. Therefore, failure to recognize insufficient thyroid hormone levels in diabetes and insulin resistance in both conditions can lead to poor patient outcomes.
Keywords: hypothyroidism, hyperthyroidism, type 2 diabetes, insulin resistance, thyroid dysfunction, thyroid cancer.